PERAN KOMUNIKASI INTERNAL DALAM MENUMBUHKAN LOYALITAS KARYAWAN DI UMKM BRUDEL UMMU AZZAM KABUPATEN GORONTALO - Antu, Nurain; Darise, Miranda; Musa, Maman; Safriandy, Mohamad (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to create a positive organizational culture, facilitate smooth operations, and build strong trust between management and employees. The research to be conducted uses a qualitative approach with a descriptive research type. Data collection techniques used are observation, interviews and documentation. The informants in the study were the shop owner and 3 employees. The data analysis techniques used were data reduction, presentation and drawing conclusions. The results of the study showed that